2019
DOI: 10.1002/jcb.29230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐337‐3p involved in the protection of CoCl2‐induced injury in PC12 cells via activating JAK2/STAT3 signaling pathway

Abstract: Objective To investigate the possibility of microRNA (miR)‐337‐3p in the protection of hypoxia‐induced injury in PC12 cells via modulating the JAK2/STAT3 signaling pathway. Methods Dual‐luciferase reporter assay analyzed the relationship between the miR‐337‐3p and JAK2. PC12 cells were divided into normal, CoCl2, CoCl2 + NC, CoCl2 + inhibitors, CoCl2 + JAK2, and CoCl2 + mimics + JAK2 groups. Then, PC12 cell viability and apoptosis were measured by the 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2H‐tetrazolium br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…In this study, we chose CoCl 2 treatment to mimic hypoxia. CoCl 2 is known as a hypoxia-mimetic agent in cell line models, as it induces biochemical and molecular reactions similar to those observed under hypoxic conditions [31][32][33][34]. In our study, we observed that with prolonged incubation with CoCl 2 , the expression of TNF-α, IL-1β, IL-6, and iNOS significantly increased in BV2 cells (Figure 1).…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we chose CoCl 2 treatment to mimic hypoxia. CoCl 2 is known as a hypoxia-mimetic agent in cell line models, as it induces biochemical and molecular reactions similar to those observed under hypoxic conditions [31][32][33][34]. In our study, we observed that with prolonged incubation with CoCl 2 , the expression of TNF-α, IL-1β, IL-6, and iNOS significantly increased in BV2 cells (Figure 1).…”
Section: Discussionsupporting
confidence: 67%
“…When cementoblasts were treated with 30 μM CoCl 2 for 24 and 48 h, HIF‐1α expression also increased in the hypoxic group compared to the control group, in a time‐dependent manner (Figure 2D). Finally, a treatment concentration of 30 μM CoCl 2 was chosen for subsequent experiments 31 …”
Section: Resultsmentioning
confidence: 99%
“…In concordance with this, high expression of hsa-miR-337-3p was associated with poor outcomes in these cancer types ( Figure 3 ). There is also experimental evidence to support the ability of this microRNA to suppress expression of JAK2 [ 29 , 30 ] via decreased luciferase activity upon co-transfection of the JAK2 3′UTR luciferase reporter and hsa-miR-337-3p, and decreased JAK2 protein levels upon overexpression of the microRNA in liver cancer cell lines. It should be noted, however, that the study by Zuo and colleagues [ 29 ] was conducted in hepatocellular carcinoma cells and hsa-miR-337-3p acted as a tumor suppressor and suppressed proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%